Translational research and applied psychology in india - Sigroha, Suman Ed; Singh, Kamlesh Ed (Sage, 2019)
"Translational research is the means by which the knowledge gained through basic scientific research can be implemented specifically for achieving a better quality of life. It seeks to provide a pathway for ideas to quickly reach the implementation stage. Translational Research has now been extended to social sciences, such as applied psychology, where focused translational research is underway in several areas, such as happiness, mental health and well-being, promoting positive cultural practices and intervention programmes. Translational Research and Applied Psychology in India focuses on research translated into real-world awareness programmes in various settings--corporate workplaces, educational, religious and social institutions, and rural areas--and even web-based interventions that are facilitating improvement in people's daily lives. This comprehensive overview of theoretical frameworks and programmes will help further functional knowledge and identify barriers between theory, practice and policy, besides bridging those barriers. This edited book is of critical importance due to the ever-increasing socio-economic differences and other related disparities that lead to ever-widening gaps in healthcare access and other such public concerns. Kamlesh Singh is Associate Professor at the Department of Humanities and Social Sciences, Indian Institute of Technology (IIT) Delhi. Suman Sigroha is Assistant Professor at the School of Humanities and Social Sciences, IIT Mandi, Himachal Pradesh"--